2013
DOI: 10.1002/ccd.24608
|View full text |Cite
|
Sign up to set email alerts
|

Transradial access for peripheral vascular interventions

Abstract: Transradial access for coronary interventions has grown substantially in the last few years. Currently, there is an increased interest in applying this approach to peripheral vascular interventions. This report reviews the current status of transradial peripheral interventions, and offers advice in terms of feasibility, equipment use, and technical challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
0
27
1
Order By: Relevance
“…There are no RCTs examining bleeding rates for TRA vs FA, so one must rely on data from this and other observational studies. Staniloae et al, 3 in a small observational study of 27 TRA vs 41 FA patients undergoing aortoiliac interventions, reported no transfusions for either group, but 7.3% had access site access, showing an 8.7% (2102 patients) rate of periprocedural blood or blood product transfusions. Given the associations between procedure-related transfusion and increased mortality, 1,[26][27][28][29] findings in such a large population warrant concern, justifying the need for RCT comparisons.…”
Section: Bleeding Complicationsmentioning
confidence: 99%
“…There are no RCTs examining bleeding rates for TRA vs FA, so one must rely on data from this and other observational studies. Staniloae et al, 3 in a small observational study of 27 TRA vs 41 FA patients undergoing aortoiliac interventions, reported no transfusions for either group, but 7.3% had access site access, showing an 8.7% (2102 patients) rate of periprocedural blood or blood product transfusions. Given the associations between procedure-related transfusion and increased mortality, 1,[26][27][28][29] findings in such a large population warrant concern, justifying the need for RCT comparisons.…”
Section: Bleeding Complicationsmentioning
confidence: 99%
“…The radial artery (RA) is the preferred access site for percutaneous coronary interventions (PCI), and it is also gaining popularity for peripheral interventions . Percutaneous iliac artery interventions (PIAI) are usually performed using the femoral or brachial artery (BA) , but limited data exists for iliac artery (IA) angioplasty performed through transradial (TR) approaches .…”
Section: Introductionmentioning
confidence: 99%
“…Upper limb access including the brachial or radial artery has several advantages compared to conventional femoral access in terms of anatomical reasons, fewer bleeding complications, and/or patient preference [5]. In common iliac artery disease, the contralateral femoral artery approach may encounter difficulty when crossing the contralateral common iliac artery lesion.…”
Section: Antegrade Upper Limb Accessmentioning
confidence: 99%